2022
DOI: 10.3389/ffunb.2022.1062444
|View full text |Cite|
|
Sign up to set email alerts
|

A survey of Fusarium species and ADON genotype on Canadian wheat grain

Abstract: IntroductionWheat is a staple food that is important to global food security, but in epidemic years, fungal pathogens can threaten production, quality, and safety of wheat grain. Globally, one of the most important fungal diseases of wheat is Fusarium head blight (FHB). This disease can be caused by several different Fusarium species with known differences in aggressiveness and mycotoxin-production potential, with the trichothecene toxin deoxynivalenol (DON) and its derivatives being of particular concern. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…With advances in low‐cost and high‐throughput DNA testing (i.e., DNA sequencing and genotyping arrays) and toxin monitoring (i.e., simple immunoassays), it is now possible to bring added value to large‐scale monitoring programmes of plant pathogens, such as ergot (Bamforth et al., 2022; Walkowiak et al., 2022). Disease monitoring programmes remain critical for understanding pathogen dynamics and emerging pathogen populations and strains so that strategies can be developed to better mitigate the disease and minimize ergot toxins in food and feed systems.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…With advances in low‐cost and high‐throughput DNA testing (i.e., DNA sequencing and genotyping arrays) and toxin monitoring (i.e., simple immunoassays), it is now possible to bring added value to large‐scale monitoring programmes of plant pathogens, such as ergot (Bamforth et al., 2022; Walkowiak et al., 2022). Disease monitoring programmes remain critical for understanding pathogen dynamics and emerging pathogen populations and strains so that strategies can be developed to better mitigate the disease and minimize ergot toxins in food and feed systems.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…A follow-up study confirmed the high prevalence of F. graminearum in eastern Canada, accounting for ~90% of nine fungal species identified in 492 spring wheat sampled between 2001 and 2017 in Ontario ( Xue et al., 2019 ). In recent years, however, F. graminearum has become the predominant causal agent of FHB not only in eastern Canada but also in the three major wheat-producing Prairie provinces of Manitoba, Saskatchewan, and Alberta ( Valverde-Bogantes et al., 2020 ; Bamforth et al., 2022 ). For example, Bamforth et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, F. graminearum has become the predominant causal agent of FHB not only in eastern Canada but also in the three major wheat-producing Prairie provinces of Manitoba, Saskatchewan, and Alberta ( Valverde-Bogantes et al., 2020 ; Bamforth et al., 2022 ). For example, Bamforth et al. (2022) studied a total of 7,783 durum and bread wheat samples originated from several farms between 2014 and 2020 in eastern and western Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation